Imperium (wciąż) odpisuje - Wiszniowska-Majchrzyk, Marta (Imperium Brytyjskie: Rozważania interdyscyplinarne, 2019)
The title of the paper refers to the work entitled The Empire Writes Back: Theory and Practice in Post-Colonial Literature (1989) by Bill Ashcroft, Gareth Grifiths and Helen Tiffin, perhaps the most influential book on colonial and postcolonial issues and the place of European perspectives in the debate. The present paper discusses three prose writers, Joseph Conrad (1857), V.S. Naipaul (b. 1932) and David Dabydeen (b. 1957), who became English writers, though neither of them was born in Britain and nor was English their native language. However, as cultural outsiders, though British citizens, living in Britain, they offered a highly original picture of both Britain and colonial and postcolonial countries. The authors were / are active in different stages in the history of the Empire, from its triumphant stage to decline. The case of Naipaul and Dabydeen indicates that what has been left from the Empire was education, which allowed them to become internationally recognized by getting acquainted with English language and culture. Conrad features prominently for both writers. The paper also discusses the once famous attack on Conrad by Chinua Achebe, which placed him in the midst of postcolonial debate, between the then living famous Nigerian writer and Conrad’s books. Empires fall but books remain, becoming their most significant cultural achievements, perhaps the only ones.